(untitled) (Plant Tissue Culture and Biotechnology, 2018)
Maximum shoot regeneration (87.85%) and number of shoots per explant in the epicotyl segments having longitudinal cut in Citrus reshni var. Cleopatra were obtained on MT medium supplemented with BAP (2 mg/l) + NAA (0.2 mg/l). Maximum shoot length (5.10 cm), average leaf number per shoot (12), leaf length (2.12 cm) and width (1.5 cm) in Cleopatra were obtained on MT medium supplemented with BAP (2 mg/l) + NAA (0.2 mg/l). The maximum in vitro rooting (78.88 %) in the excised shoots occurred in liquid medium on MS supplemented with BAP (0.5 mg/l) + NAA (0.5 mg/l). Plant Tissue Cult. & Biotech. 28(2): 251-260, 2018 (December)